Myocardial Perfusion Imaging - Beyond the Left Ventricle : Pathology, Artifacts and Pitfalls in the Chest and Abdomen - Oates, M. Elizabeth; Sorrell, Vincent L. (Springer International Publishing : Imprint: Springer, 2017)
This book will serve as a comprehensive reference source and self-assessment guide for physicians and technologists who practice myocardial perfusion SPECT imaging. Readers will learn to identify a wide variety of findings apart from the left ventricle, including those in the chest, the abdomen, and the right heart. It is explained which findings are clinically relevant and related to the reason for the myocardial perfusion imaging examination and which are incidental, with or without important clinical ramifications. The coverage includes a wide variety of common and uncommon focal lesions (e.g., benign or malignant neoplasms) and organ/systemic diseases (e.g., emphysema, cirrhosis and its sequelae, cholecystitis, duodenogastric reflux/gastroparesis, end-stage renal disease) that may be detected with myocardial perfusion SPECT imaging. In addition, guidance is provided in the recognition of typical artifacts, which may appear either "hot" or "cold" on the raw (unprocessed) and processed SPECT images, and, thereby, in the avoidance of potential interpretative pitfalls.- Resumé vydavatel
Keywords: srdce; radiologie; nukleární medicína; kardiologie; heart; radiology; nuclear medicine; cardiology; elektronické knihy; příručky; electronic books; handbooks and manuals